Biomechanical comparison of anterior cruciate ligament repair with internal brace augmentation versus anterior cruciate ligament repair without augmentation. (July 2020) - Massey, Patrick; Parker, David; McClary, Kaylan; Robinson, James; Barton, R. Shane; Solitro, Giovanni F.
Abstract: Background: Newer repair techniques of anterior cruciate ligament tears, including augmentation with internal brace, have shown promising clinical results. Few biomechanical studies exist comparing anterior cruciate ligament repair only versus repair with internal brace. The purpose of this study was to compare the load to failure and stiffness of anterior cruciate ligament repair with internal brace augmentation versus repair-only. Methods: Proximal femoral avulsion type anterior cruciate ligament injuries were created in 20 cadaver knees. Anterior cruciate ligament repair-only or repair with internal brace was performed using arthroscopic tools. Load to failure and failure modes were collected, with calculations of stiffness and energy to failure performed. Findings: The average load to failure for the internal brace group was higher than the repair-only group: 693 N (SD 248) versus 279 N (SD 91), P  = .002. The stiffness and energy to failure values were higher for the internal brace group than the repair-only group: 83 N/mm versus 58 N/mm, P  = .02 and 16.88 J (SD 12.44) versus 6.91 J (SD 2.49), P  = .04, respectively. Failure modes differed between groups ( P  = .00097) with 80% failure in the repair-only due to suture pull through the anterior cruciate ligament and 90% failure in the internal brace group due to suture button pull through the femur. Interpretation: There was higher load to failure, stiffness, and energy to failure for the internal brace group compared to the repair-only group, and a high positive correlation between bone density and load to failure for the internal brace group. Clinical significance: Anterior cruciate ligament repair with internal brace augmentation demonstrates significantly higher load to failure. It may be a useful adjunct to protect the anterior cruciate ligament repair from failure during the early stages of healing. Highlights: The failure load of anterior cruciate ligament repair with Internal Brace Augmentation is high. Higher load to failure for anterior cruciate ligament repair with augmentation than without. There is higher stiffness for the anterior cruciate ligament repair with Internal Brace. There is more energy until failure for anterior cruciate ligament repair with Internal Brace. Different mode of failure for anterior cruciate ligament repair augmented with Internal Brace.